Do Models Improve Fishery Management? Empirical Evidence from a Experimental Study - Kjell Arne Brekke; Erling Moxnes (Statistics Norway, Research Department, 1998)
At the initial stage of this project, the project group consisted of Asbjørn Aaheim, Magnus Hatlebakk and the authors. The authors are grateful for the discussion with the other project participants at this stage. We also had very useful discussion with the marine researcher Sigurd Tjelmeland about the design of the virtual reality. Thanks also to Solfrid Malo for assistance during some of the experiments. Ådne Cappelen, Øystein Olsen and Karine Nyborg has given helpful comments on an earlier draft of the paper. The usual disqualifier applies.
Keywords: A11; C9; Q22; 330; Experiment; theory management